2018
DOI: 10.1007/s00428-018-2341-1
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver variability in the H&E-based assessment of tumor budding in pT3/4 colon cancer: does it affect the prognostic relevance?

Abstract: Tumor budding is a mostly accepted adverse prognostic factor in colorectal carcinoma. It is on the cusp of a widespread use after agreement was reached recently on uniform assessment criteria. We investigated whether the interobserver variability has a direct influence on the prognostic relevance in pT3/4 colon cancer in the background of different levels of experience of the investigators. In total, six investigators with different levels of experience evaluated tumor budding on H&E slides in 244 cases with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 29 publications
2
40
1
Order By: Relevance
“…In this context it is worth emphasising that most investigators of this study were residents. Moreover, the training period was limited . Following the idea that the question of ‘how difficult is the assessment?’ is a risk stratification, there has to be a consequence for D3/Li3 classified cases.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In this context it is worth emphasising that most investigators of this study were residents. Moreover, the training period was limited . Following the idea that the question of ‘how difficult is the assessment?’ is a risk stratification, there has to be a consequence for D3/Li3 classified cases.…”
Section: Discussionmentioning
confidence: 99%
“…Following the idea that the question of ‘how difficult is the assessment?’ is a risk stratification, there has to be a consequence for D3/Li3 classified cases. The mandatory dialogue and the corporate assessment, together with a colleague, might provide a better assessment quality and cytokeratin staining might be helpful in these cases. However, it has to be shown that the two techniques in fact have a measurably reductive effect on the interobserver variability in these cases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations